The national Creole project in Memoires by Tupac Amaru and Autobiography by Manzano. (Anclajes, 2020)
Juan Bautista Tupac Amaru and Juan Francisco Manzano’s narratives demonstrate their authors’ suffering vis-à-vis the injustices they experienced. However, both narratives are mediated by the Creole political elite, both in Argentina and Cuba, in support of the nation-state being forged at the turn of the 19th century. Upon analyzing their statements, the narratives of these two men, one of native Indian heritage and the other of African descent, appear to have undergone a suspicious acculturation in an effort to build a utopian national unity conceived by white criollos.
Keywords: Narratives; nation-state; Juan Bautista Tupac Amaru; Juan Francisco Manzano; 19th century